Treasury and Post Office, B.W.I. 18 - (:unkn) unknown (My University, 2010)
Photo of the Treasury and General Post Office building located in Port of Spain, Trinidad. A Government of Trinidad and Tobago insignia is seen on the wall just above the entrance to the building. The hillside can be seen in the distant background.
Colour: Black and White ; Style: Landscape ; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Public buildings; Postal service; Treasury